Occupational safety and health practice: a study at construction of large water tank - Ahmad, Nurul Fazilawati Hawa; Shafai@Shafie, Siti Nor Zulaikha; Ibrahim, Nur Hanisah; Mahmood, Salwa; Khalid, Amir; Jaat, Norrizam; Ngadiron, Zuraidah (Penerbit UTHM, 2020)
The Occupational Health and Safety Act (OSHA) provide for the health, safety and welfare of persons employed, and all persons lawfully present at workplaces and related matters. It is obligatory for an occupier to provide and maintain plant and systems and procedures of work that are safe and without risk to workers' health. This study emphasizes on the identification of hazards, the hazard evaluation process, and the control measures taken to prevent accidents located at Taman Maju, Kelantan. That has a lot of hazard at the construction site. It is because of a lack of management control often leads to the existence of causes of accidents and allows for unsafe practices among the workers. Lack of awareness among the worker and companies about safety and hazard in the construction site. This project focuses on the effects of risk assessment (HIRARC) on organizational performance in the site is a structured approach for identifying, evaluating and controlling hazards in the construction site with a view to achieving better organizational performance of no harm/damage to people, assets, environment and reputation. The objective of this study is to ascertain the extent of compliance and influence on organizational performance such reduced accident/ incident rate, improved safety practices, enhanced productivity and increased profitability of risk assessment (HIRARC) in the construction site. For the methodology, the study had been conducted based on observation and analysis in order to accomplish this project to instruments by using HIRARC form. For the result and discussion. the hazard had been analysed and recommendation for precaution need to be taken had been proposed. Workplace and work environment that is safe, without health risks and adequate as regards facilities and arrangements for the worker's welfare at work can have the better performance and it will make the job become more efficient.